Effects of a nurse-led peer support intervention for stroke survivors: protocol for a randomised controlled trial - Ying Wu; Janita Pak Chun Chau; Xiaojuan Wan; Limei Xu; Weijuan Gong (BMJ Open)
Introduction Many stroke survivors have unmet psychosocial needs during the recovery phase following a stroke. There is emerging evidence that peer support interventions may play a valuable role in managing stroke. However, evidence regarding the effectiveness of peer support interventions on the psychosocial outcomes of stroke survivors is uncertain. This study aims to develop a nurse-led peer support intervention for stroke survivors based on the Person–Environment–Occupation–Performance Model and evaluate its effects on the psychosocial outcomes of stroke survivors.Methods and analysis This is an assessor-blinded two-arm randomised controlled trial. A convenience sample of 120 stroke survivors will be recruited from two community centres and one rehabilitation unit in Yangzhou, a medium-sized city in eastern China, with 60 participants each in the intervention and control groups. The participants allocated to the intervention group will receive the nurse-led peer support intervention, which includes 6 weekly peer support sessions facilitated by a nurse and at least one peer facilitator. Participants randomised to the control group will receive the same dose of interpersonal interaction as intervention participants, including weekly individual face-to-face session for 6 weeks. The primary outcomes are social participation and participation self-efficacy. The secondary outcomes are psychosocial distress, social support, stigma towards disease, self-efficacy in managing chronic conditions and quality of life. Data will be collected at baseline, immediately after the intervention and 3 months after the intervention. A process evaluation will be conducted qualitatively and quantitively to examine the mechanism by which the intervention impacts the psychosocial outcomes of stroke survivors. All outcomes will be analysed following the intention to treat principle. Generalised Estimation Equation models will be used to assess the intervention effect.Ethics and dissemination This protocol was approved by the Joint Chinese University of Hong Kong-New Territories East Cluster Clinical Research Ethics Committee (CREC Ref. No.: 2021.196-T). All participants will be required to provide written informed consent. Results of the study will be disseminated through publication in peer-reviewed journals and presentation at local or international conferences.Trial registration number ChiCTR2100050853.